Analisis Waktu Tunggu Pelayanan Poliklinik Rawat Jalan di Rumah Sakit - Setiyawati, Florensiya Fina; Kurnianto, Andreas; Putriyanti, C. Ermayani (Jurnal Kesehatan, 2024)
A hospital provides complete individual health services, including inpatient, outpatient and emergency services. Hospital outpatient services are health services provided in polyclinics. Based on the Health Ministry data in 2007, the ideal outpatient service time is less than 60 minutes. However, in practice, there are still services in polyclinics that exceed the standard time that has been set. Long waiting times can result in boredom, dissatisfaction with service for patients, and the potential for complaints. This study aims to analyze the waiting times for polyclinic patients in several hospitals and determine the causes of waiting times exceeding the provisions. This research uses a literature review method, which involves reviewing several journal articles. The data found resulted from a Google Scholar-based literature review of articles using the keywords: waiting time, waiting time analysis, and polyclinic waiting time, with a journal publication time limit of 2019 to 2023. There were 8 articles that met the criteria. Based on the results of the analysis, it was found that there are still many services in polyclinics with waiting times of more than 60 minutes. The causes of waiting times exceeding those set by the Health Ministry in 2007 include the length of time in providing medical record files, the length of the patient examination process, the queues for patient registration piling up, and doctor delays. Hospitals that find cases of long waiting times are expected to be able to create new systems or regulations that are expected to be able to improve existing services related to patient waiting times in polyclinics.